Joaquín Gallegos Lara y «El síndrome de Falcón»: literatura, mestizaje e interculturalidad en el Ecuador - Handelsman, Michael (2009)
Ecuadorian writers have created a rich legacy of characters who point towards a national identity that is, ultimately, multi-national and inter-cultural. Although the authors of the 1930’s generation proposed through their fiction a notion of nation that included all of the different cultures within it –it was a failed miscegenation project as it eliminated differences while reinforcing inequalities–, the social role of these groups during the 90’s complements that proposed by the literature of the 30’s. Additionally, the political self representation of these groups calls into question the criteria of the contemporary cultural context exemplified by the «The Falcon Syndrome», which seeks to be a metaphor for the burden of representing socially disadvantaged groups, which has weighed heavily over Ecuadorian writers throughout the 20th century. All of this propels the reconfiguration process within the panorama of Ecuadorian culture: the growing participation of the long-silenced voices, as well as the emergence of other ways to look upon the world, allows for new readings of classic novels such as Don Goyo or La isla virgen, by Demetrio Aguilera-Malta.